Gallate-based near-infrared luminescent material capable of being excited by blue light LED and preparation method and application of gallate-based near-infrared luminescent material
By using Cr3+-doped gallium salt matrix materials, gallium salt-based near-infrared luminescent materials suitable for blue LED excitation were prepared, overcoming the shortcomings of existing materials in terms of spectral bandwidth and luminous efficiency, and realizing the emission of efficient broadband near-infrared light to meet the needs of portable near-infrared LED light sources.
Patent Information
- Application Number
- CN202510826106.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-19
- Publication Date
- 2025-11-21
AI Technical Summary
Existing near-infrared light source materials have not fully met the needs of practical applications in terms of spectral bandwidth and luminous efficiency. Traditional light sources have problems such as low energy efficiency, poor spectral tunability, and bulky size, making it difficult to meet the needs of portable high-performance near-infrared LED light sources.
By using Cr3+-doped gallium salt matrix material and exciting it with blue LED, a gallium salt-based near-infrared luminescent material suitable for blue LED excitation was prepared, achieving efficient broadband near-infrared light emission.
It achieves high-efficiency broadband near-infrared light emission with a quantum efficiency close to 100%, meeting the needs of portable near-infrared LED light sources. The process is simple and the product has high stability.
Smart Images

Figure CN120988699A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of inorganic light-emitting materials technology, and more specifically, relates to a gallate-based near-infrared light-emitting material that can be excited by blue LEDs, its preparation method and application. Technical Background
[0002] Near-infrared spectroscopy, as a non-invasive analytical technique, utilizes the characteristic molecular vibrations of different functional groups, giving it the unique advantages of non-destructive and real-time detection. Based on this, near-infrared LED light sources have been widely used in optical communication, biomedical imaging, and non-destructive testing. Meanwhile, with the development of portable intelligent detection devices, traditional near-infrared light sources, such as halogen lamps and semiconductor lasers, suffer from inherent defects such as low energy efficiency, poor spectral tunability, and bulky size, making it difficult to meet the urgent demands of modern dynamic detection systems for miniaturized and integrated light sources.
[0003] Against this backdrop, portable near-infrared LED light sources based on phosphor conversion, as a novel type of intelligent solid-state light source, are gradually becoming the mainstream technology to replace traditional light sources due to their high energy efficiency, small size, compact structure, light weight, and wide spectral tunability. This technology involves coating different phosphors onto an LED chip, which then excites the phosphors to emit near-infrared light, thus achieving near-infrared light emission over a wide wavelength range to meet diverse application needs. In this process, gallium ester materials are considered ideal carriers for constructing high-efficiency phosphors due to their excellent structural stability. In recent years, researchers have achieved partial near-infrared emission in gallium ester systems through ion doping strategies, but existing materials still fail to fully meet practical application requirements in terms of spectral bandwidth and luminous efficiency. Therefore, the development of long-wavelength, broadband, and high quantum-efficiency near-infrared phosphors has become a research hotspot. Simultaneously, the increasing market demand for portable high-performance near-infrared LED light sources has driven the urgent need to develop novel high-performance near-infrared luminescent materials that can be excited by blue light. Summary of the Invention
[0004] To address the shortcomings and drawbacks of the existing technology, the present invention aims to provide a gallium-based near-infrared luminescent material that can be excited by a blue LED, wherein the luminescent material is Cr. 3+ Inorganic light-emitting materials doped with gallium salt matrix.
[0005] Another object of the present invention is to provide a method for preparing the above-mentioned gallium-based near-infrared luminescent material that can be excited by blue LEDs. This method synthesizes a luminescent material suitable for blue LED excitation by doping a gallium-based matrix material with trivalent chromium ions, achieving efficient broadband near-infrared light emission.
[0006] Another object of the present invention is to provide the application of the above-mentioned gallium-based near-infrared luminescent material that can be excited by blue LEDs. This near-infrared luminescent material is suitable for generating the required high-efficiency near-infrared light when excited by blue LEDs.
[0007] The objective of this invention is achieved through the following technical solution:
[0008] A gallium-based near-infrared luminescent material exciteable by blue LEDs has the molecular formula Ba2M2NGa. 10-x Al x O 22 :yCr 3+ Where M is Sn, Zr or Hf, and N is Mg or Zn; 0 ≤ x ≤ 10; 0 < y ≤ 2.
[0009] The method for preparing the gallium-based near-infrared luminescent material exciteable by blue LED includes the following specific steps:
[0010] S1. Mix and grind barium compound, M compound, N compound, gallium compound and / or aluminum compound, chromium compound and cosolvent boric acid until homogeneous to obtain a mixture;
[0011] S2. The mixture is pre-calcined in air at 800-900°C, then ground after cooling to room temperature, and then calcined at 1400-1500°C to obtain a gallium-based near-infrared luminescent material that can be excited by blue LEDs.
[0012] Preferably, the barium compound in step S1 is barium carbonate, barium nitrate, or barium oxide.
[0013] Preferably, the compound M in step S1 is tin nitrate, zirconium nitrate, hafnium nitrate, tin dioxide, zirconium dioxide, or hafnium dioxide.
[0014] Preferably, the N compound in step S1 is zinc carbonate, magnesium carbonate, zinc nitrate, magnesium nitrate, zinc oxalate, magnesium oxalate, zinc oxide, or magnesium oxide.
[0015] Preferably, the gallium compound in step S1 is one or more of gallium nitrate, gallium oxalate, or gallium oxide; and the aluminum compound is one or more of aluminum nitrate, aluminum oxalate, or aluminum oxide.
[0016] Preferably, the chromium compound in step S1 is chromium nitrate and / or chromium oxide.
[0017] Preferably, the pre-firing time in step S2 is 4-6 hours, and the calcination time is 6-8 hours.
[0018] The application of the gallate-based near-infrared luminescent material that can be excited by blue LEDs in the field of blue LED chip fabrication.
[0019] Compared with the prior art, the present invention has the following beneficial effects:
[0020] 1. The gallium-based near-infrared luminescent material of the present invention is Cr 3+ An inorganic light-emitting material based on a single gallium salt matrix, which can be excited by blue light and is suitable for blue LED chips, can generate highly efficient near-infrared light with a quantum efficiency close to 100%, meeting the needs of portable near-infrared LED light sources based on phosphor conversion.
[0021] 2. This invention synthesizes a light-emitting material suitable for excitation by blue LEDs by using trivalent chromium ion-doped gallium salt matrix material, achieving efficient broadband near-infrared light emission; the process is simple, the synthesis process is easy to control, and the product has high stability. Attached Figure Description
[0022] Figure 1 This is the X-ray diffraction pattern of the luminescent material prepared in Example 1.
[0023] Figure 2 The images show the excitation and emission spectra of the luminescent material prepared in Example 1.
[0024] Figure 3 These are the excitation and emission spectra of the luminescent material prepared in Example 2.
[0025] Figure 4 These are the excitation and emission spectra of the luminescent material prepared in Example 3.
[0026] Figure 5 These are the excitation and emission spectra of the luminescent material prepared in Example 4.
[0027] Figure 6 These are the excitation and emission spectra (a) and quantum efficiency spectra (b) of the luminescent material prepared in Example 5.
[0028] Figure 7 These are the excitation and emission spectra of the luminescent material prepared in Example 6.
[0029] Figure 8 These are the excitation and emission spectra of the luminescent material prepared in Example 7.
[0030] Figure 9 These are the excitation and emission spectra of the luminescent material prepared in Example 8.
[0031] Figure 10 The excitation and emission spectra are those of the luminescent material prepared in Example 10.
[0032] Figure 11 The excitation and emission spectra are those of the luminescent material prepared in Example 11. Detailed Implementation
[0033] The present invention will be further described below with reference to specific embodiments, but these should not be construed as limiting the invention. Unless otherwise specified, the technical means used in the embodiments are conventional means well known to those skilled in the art. Unless otherwise specified, the reagents, methods, and equipment used in the present invention are conventional reagents, methods, and equipment in this technical field.
[0034] Example 1
[0035] According to chemical composition: Ba2Sn2ZnGa 10 O 22 0.01Cr 3+ Barium carbonate, tin dioxide, zinc oxide, gallium oxide, chromium trioxide, and boric acid were weighed separately, thoroughly mixed and ground until homogeneous. The resulting mixture was placed in a corundum crucible and then placed in a muffle furnace. It was pre-calcined at 800°C for 4 hours in air atmosphere. After natural cooling to room temperature, it was removed and ground again until homogeneous. Then, it was placed in a tube furnace and calcined at 1400°C for 6 hours. After natural cooling to room temperature, it was removed and ground again to obtain the luminescent material Ba₂Sn₂ZnGa. 10 O 22 0.01Cr 3+ .
[0036] Figure 1 The X-ray diffraction pattern of the luminescent material prepared in this embodiment is shown below. Figure 2 The excitation and emission spectra of the luminescent material prepared in this embodiment are shown. Figure 1 As can be seen from this, the luminescent material prepared in this embodiment is a pure phase. Figure 2 It can be seen that the excitation wavelength of the luminescent material prepared in this embodiment is 438nm and the emission wavelength is 740nm.
[0037] Example 2
[0038] According to chemical composition: Ba2Sn2ZnGa 10 O 22 0.02Cr 3+ Barium carbonate, tin dioxide, zinc oxide, gallium oxide, chromium trioxide, and boric acid were weighed separately, thoroughly mixed and ground until homogeneous. The resulting mixture was placed in a corundum crucible and then placed in a muffle furnace. It was pre-calcined at 800°C for 4 hours in air atmosphere. After naturally cooling to room temperature, it was removed and ground again until homogeneous. Then, it was placed in a tube furnace and heated to 1400°C for 6 hours. After naturally cooling to room temperature, it was removed and ground again to obtain the luminescent material Ba₂Sn₂ZnGa. 10 O 22 0.02Cr 3+ .
[0039] Figure 3The excitation and emission spectra of the luminescent material prepared in this embodiment are shown. Figure 3 As can be seen from the above, the excitation wavelength of the luminescent material prepared in this embodiment is 438 nm, and the emission wavelength is 743 nm.
[0040] Example 3
[0041] According to chemical composition: Ba2Sn2ZnGa 10 O 22 0.03Cr 3+ Barium carbonate, tin dioxide, zinc oxide, gallium oxide, chromium trioxide, and boric acid were weighed separately, thoroughly mixed and ground until homogeneous. The resulting mixture was placed in a corundum crucible and then placed in a muffle furnace. It was pre-calcined at 800℃ for 4 hours in air atmosphere. After naturally cooling to room temperature, it was removed and ground again until homogeneous. Then, it was placed in a tube furnace and calcined at 1400℃ for 6 hours. After naturally cooling to room temperature, it was removed and ground again to obtain the luminescent material Ba₂Sn₂ZnGa. 10 O 22 0.03Cr 3+ .
[0042] Figure 4 The excitation and emission spectra of the luminescent material prepared in this embodiment are shown. Figure 4 As can be seen from the above, the excitation wavelength of the luminescent material prepared in this embodiment is 438 nm, and the emission wavelength is 745 nm.
[0043] Example 4
[0044] According to chemical composition: Ba2Sn2ZnGa 10 O 22 0.04Cr 3+ Barium carbonate, tin dioxide, zinc oxide, gallium oxide, chromium trioxide, and boric acid were weighed separately, thoroughly mixed and ground until homogeneous. The resulting mixture was placed in a corundum crucible and then placed in a muffle furnace. It was pre-calcined at 800°C for 4 hours in air atmosphere. After naturally cooling to room temperature, it was removed and ground again until homogeneous. Then, it was placed in a tube furnace and calcined at 1400°C for 6 hours. After naturally cooling to room temperature, it was removed and ground again to obtain the luminescent material Ba₂Sn₂ZnGa. 10 O 22 0.04Cr 3+ .
[0045] Figure 5 The excitation and emission spectra of the luminescent material prepared in this embodiment are shown. Figure 5 As can be seen from the above, the excitation wavelength of the luminescent material prepared in this embodiment is 438 nm, and the emission wavelength is 747 nm.
[0046] Example 5
[0047] According to chemical composition: Ba2Sn2ZnGa 10 O 22 0.05Cr 3+ Barium carbonate, tin dioxide, zinc oxide, gallium oxide, chromium trioxide, and boric acid were weighed separately, thoroughly mixed and ground until homogeneous. The resulting mixture was placed in a corundum crucible and then placed in a muffle furnace. It was pre-calcined at 800°C for 4 hours in air atmosphere. After naturally cooling to room temperature, it was removed and ground again until homogeneous. Then, it was placed in a tube furnace and calcined at 1400°C for 6 hours. After naturally cooling to room temperature, it was removed and ground again to obtain the luminescent material Ba₂Sn₂ZnGa. 10 O 22 0.05Cr 3+ .
[0048] Figure 6 The excitation and emission spectra (a) and quantum efficiency spectrum (b) of the luminescent material prepared for this embodiment are shown. Figure 6 As can be seen from the data, the excitation wavelength of the luminescent material prepared in this embodiment is 438 nm, the emission wavelength is 748 nm, and the internal quantum efficiency, external quantum efficiency, and absorption efficiency are 99.44%, 30.12%, and 30.29%, respectively.
[0049] Example 6
[0050] According to chemical composition: Ba2Sn2ZnGa 10 O 22 0.06Cr 3+ Barium carbonate, tin dioxide, zinc oxide, gallium oxide, chromium trioxide, and boric acid were weighed separately, thoroughly mixed and ground until homogeneous. The resulting mixture was placed in a corundum crucible and then placed in a muffle furnace. It was pre-calcined at 800°C for 4 hours in air atmosphere. After naturally cooling to room temperature, it was removed and ground again until homogeneous. Then, it was placed in a tube furnace and calcined at 1400°C for 6 hours. After naturally cooling to room temperature, it was removed and ground again to obtain the luminescent material Ba₂Sn₂ZnGa. 10 O 22 0.06Cr 3+ .
[0051] Figure 7 The excitation and emission spectra of the luminescent material prepared in this embodiment are shown. Figure 7 As can be seen from the above, the excitation wavelength of the luminescent material prepared in this embodiment is 438 nm, and the emission wavelength is 749 nm.
[0052] Example 7
[0053] According to chemical composition: Ba2Sn2ZnGa 10 O 22 0.15Cr 3+Barium carbonate, tin dioxide, zinc oxide, gallium oxide, chromium trioxide, and boric acid were weighed separately, thoroughly mixed and ground until homogeneous. The resulting mixture was placed in a corundum crucible and then placed in a muffle furnace. It was pre-calcined at 800°C for 4 hours in air atmosphere. After naturally cooling to room temperature, it was removed and ground again until homogeneous. Then, it was placed in a tube furnace and calcined at 1400°C for 6 hours. After naturally cooling to room temperature, it was removed and ground again to obtain the luminescent material Ba₂Sn₂ZnGa. 10 O 22 0.15Cr 3+ .
[0054] Figure 8 The excitation and emission spectra of the luminescent material prepared in this embodiment are shown. Figure 8 As can be seen from the above, the excitation wavelength of the luminescent material prepared in this embodiment is 438 nm, and the emission wavelength is 753 nm.
[0055] Example 8
[0056] According to chemical composition: Ba2Sn2ZnGa 10 O 22 0.20Cr 3+ Barium carbonate, tin dioxide, zinc oxide, gallium oxide, chromium trioxide, and boric acid were weighed separately, thoroughly mixed and ground until homogeneous. The resulting mixture was placed in a corundum crucible and then placed in a muffle furnace. It was pre-calcined at 800°C for 4 hours in air atmosphere. After naturally cooling to room temperature, it was removed and ground again until homogeneous. Then, it was placed in a tube furnace and calcined at 1400°C for 6 hours. After naturally cooling to room temperature, it was ground again to obtain the luminescent material Ba₂Sn₂ZnGa. 10 O 22 0.20Cr 3+ .
[0057] Figure 9 The excitation and emission spectra of the luminescent material prepared in this embodiment are shown. Figure 9 As can be seen from the above, the excitation wavelength of the luminescent material prepared in this embodiment is 438 nm, and the emission wavelength is 757 nm.
[0058] Example 9
[0059] According to chemical composition: Ba2Sn2ZnGa 10 O 22 0.5Cr 3+Barium carbonate, tin dioxide, zinc oxide, gallium oxide, chromium trioxide, and boric acid were weighed separately, thoroughly mixed and ground until homogeneous. The resulting mixture was placed in a corundum crucible, placed in a muffle furnace, and pre-calcined at 800℃ for 4 hours in an air atmosphere. After naturally cooling to room temperature, it was removed, ground again until homogeneous, and then placed in a tube furnace and calcined at 1400℃ for 6 hours. After naturally cooling to room temperature, it was ground again to obtain the luminescent material Ba2Sn2ZnGa. 10 O 22 0.5Cr 3+ .
[0060] Example 10
[0061] According to chemical composition: Ba2Sn2ZnGa 9.5 Al 0.5 O 22 0.5Cr 3+ Barium carbonate, tin dioxide, zinc oxide, gallium oxide, chromium trioxide, and boric acid were weighed separately, thoroughly mixed and ground until homogeneous. The resulting mixture was placed in a corundum crucible, placed in a muffle furnace, and pre-calcined at 800℃ for 4 hours in an air atmosphere. After naturally cooling to room temperature, it was removed, ground again until homogeneous, and then placed in a tube furnace and calcined at 1400℃ for 6 hours. After naturally cooling to room temperature, it was ground again to obtain the luminescent material Ba2Sn2ZnGa. 9.5 Al 0.5 O 22 0.5Cr 3+ .
[0062] Figure 10 The excitation and emission spectra of the luminescent material prepared in this embodiment are shown. Figure 10 As can be seen from the above, the excitation wavelength of the luminescent material prepared in this embodiment is 435nm and the emission wavelength is 763nm.
[0063] Example 11
[0064] According to chemical composition: Ba2Sn2Zn 0.5 Mg 0.5 Ga 9.5 Al 0.5 O 22 0.5Cr 3+ Barium carbonate, tin dioxide, zinc oxide, magnesium oxide, gallium oxide, chromium trioxide, and boric acid were weighed separately, thoroughly mixed and ground until homogeneous. The resulting mixture was placed in a corundum crucible and then placed in a muffle furnace. It was pre-calcined at 800°C for 5 hours in air atmosphere. After naturally cooling to room temperature, it was removed and ground again until homogeneous. Then, it was placed in a tube furnace and calcined at 1450°C for 6 hours. After naturally cooling to room temperature, it was ground again to obtain the luminescent material Ba₂Sn₂Zn. 0.5 Mg0.5 Ga 9.5 Al 0.5 O 22 0.5Cr 3+ .
[0065] Figure 11 The excitation and emission spectra of the luminescent material prepared in this embodiment are shown. Figure 11 As can be seen from the above, the excitation wavelength of the luminescent material prepared in this embodiment is 439 nm, and the emission wavelength is 768 nm.
[0066] Example 12
[0067] According to chemical composition: Ba2Sn2MgGa 10 O 22 0.5Cr 3+ Barium carbonate, tin dioxide, magnesium oxide, gallium oxide, chromium trioxide, and boric acid were weighed separately, thoroughly mixed and ground until homogeneous. The resulting mixture was placed in a corundum crucible, placed in a muffle furnace, and pre-calcined at 800℃ for 5 hours in air atmosphere. After naturally cooling to room temperature, it was removed, ground again until homogeneous, and then placed in a tube furnace and calcined at 1500℃ for 8 hours. After naturally cooling to room temperature, it was ground again to obtain the luminescent material Ba2Sn2MgGa. 10 O 22 0.5Cr 3+ .
[0068] Example 13
[0069] According to chemical composition: Ba2Sn2MgGa8Al2O 22 0.5Cr 3+ Barium carbonate, tin dioxide, magnesium oxide, gallium oxide, aluminum oxide, chromium trioxide, and boric acid were weighed separately, thoroughly mixed and ground until homogeneous. The resulting mixture was placed in a corundum crucible and then placed in a muffle furnace. It was pre-calcined at 800℃ for 5 hours in air atmosphere. After naturally cooling to room temperature, it was removed and ground again until homogeneous. Then, it was placed in a tube furnace and calcined at 1500℃ for 8 hours. After naturally cooling to room temperature, it was ground again to obtain the luminescent material Ba2Sn2MgGa8Al2O. 22 0.5Cr 3+ .
[0070] Example 14
[0071] According to chemical composition: Ba2Sn2MgGa6Al4O 22 0.5Cr 3+Barium carbonate, tin dioxide, magnesium oxide, gallium oxide, aluminum oxide, chromium trioxide, and boric acid were weighed separately, thoroughly mixed and ground until homogeneous. The resulting mixture was placed in a corundum crucible and then placed in a muffle furnace. It was pre-calcined at 800℃ for 5 hours in air atmosphere. After naturally cooling to room temperature, it was removed and ground again until homogeneous. Then, it was placed in a tube furnace and calcined at 1500℃ for 8 hours. After naturally cooling to room temperature, it was ground again to obtain the luminescent material Ba2Sn2MgGa6Al4O. 22 0.5Cr 3+ .
[0072] Example 15
[0073] According to chemical composition: Ba2Sn2MgGa4Al6O 22 0.5Cr 3+ Barium carbonate, tin dioxide, magnesium oxide, gallium oxide, aluminum oxide, chromium trioxide, and boric acid were weighed separately, thoroughly mixed and ground until homogeneous. The resulting mixture was placed in a corundum crucible and then placed in a muffle furnace. It was pre-calcined at 800℃ for 5 hours in air atmosphere. After naturally cooling to room temperature, it was removed and ground again until homogeneous. Then, it was placed in a tube furnace and calcined at 1500℃ for 8 hours. After naturally cooling to room temperature, it was ground again to obtain the luminescent material Ba2Sn2MgGa4Al6O. 22 0.5Cr 3+ .
[0074] Example 16
[0075] According to chemical composition: Ba2Sn2MgGa2Al8O 22 0.5Cr 3+ Barium carbonate, tin dioxide, magnesium oxide, gallium oxide, aluminum oxide, chromium trioxide, and boric acid were weighed separately, thoroughly mixed and ground until homogeneous. The resulting mixture was placed in a corundum crucible and then placed in a muffle furnace. It was pre-calcined at 800℃ for 5 hours in air atmosphere. After naturally cooling to room temperature, it was removed and ground again until homogeneous. Then, it was placed in a tube furnace and calcined at 1500℃ for 8 hours. After naturally cooling to room temperature, it was ground again to obtain the luminescent material Ba2Sn2MgGa2Al8O. 22 0.5Cr 3+ .
[0076] Example 17
[0077] According to chemical composition: Ba2Sn2MgAl 10 O 22 0.5Cr 3+Barium carbonate, tin dioxide, magnesium oxide, aluminum oxide, chromium trioxide, and boric acid were weighed separately, thoroughly mixed and ground until homogeneous. The resulting mixture was placed in a corundum crucible and then placed in a muffle furnace. It was pre-calcined at 800℃ for 5 hours in air atmosphere. After naturally cooling to room temperature, it was removed and ground again until homogeneous. Then, it was placed in a tube furnace and calcined at 1500℃ for 8 hours. After naturally cooling to room temperature, it was ground again to obtain the luminescent material Ba2Sn2MgAl. 10 O 22 0.5Cr 3+ .
[0078] Example 18
[0079] According to chemical composition: Ba2SnZrMgGa8Al2O 22 0.5Cr 3+ Barium carbonate, tin dioxide, zirconium dioxide, magnesium oxide, gallium oxide, aluminum oxide, chromium trioxide, and boric acid were weighed separately, thoroughly mixed and ground until homogeneous. The resulting mixture was placed in a corundum crucible and then placed in a muffle furnace. It was pre-calcined at 850°C for 5 hours in air atmosphere. After naturally cooling to room temperature, it was removed and ground again until homogeneous. Then, it was placed in a tube furnace and calcined at 1500°C for 8 hours. After naturally cooling to room temperature, it was ground again to obtain the luminescent material Ba₂SnZrMgGa₈Al₂O. 22 0.5Cr 3+ .
[0080] Example 19
[0081] According to chemical composition: Ba2SnHfMgGa8Al2O 22 0.5Cr 3+ Barium carbonate, tin dioxide, hafnium dioxide, magnesium oxide, gallium oxide, aluminum oxide, chromium trioxide, and boric acid were weighed separately, thoroughly mixed and ground until homogeneous. The resulting mixture was placed in a corundum crucible and then placed in a muffle furnace. It was pre-calcined at 900℃ for 6 hours in air atmosphere. After naturally cooling to room temperature, it was removed and ground again until homogeneous. Then, it was placed in a tube furnace and calcined at 1500℃ for 8 hours. After naturally cooling to room temperature, it was ground again to obtain the luminescent material Ba2SnHfMgGa8Al2O. 22 0.5Cr 3+ .
[0082] The gallium-based near-infrared luminescent material of this invention is Cr 3+ An inorganic light-emitting material based on a single gallium salt matrix, which can be excited by blue light and is suitable for blue LED chips, can generate highly efficient near-infrared light with a quantum efficiency close to 100%, meeting the needs of portable near-infrared LED light sources based on phosphor conversion.
[0083] The above embodiments are preferred embodiments of the present invention, but the embodiments of the present invention are not limited to the above embodiments. Any changes, modifications, substitutions, combinations and simplifications made without departing from the spirit and principle of the present invention shall be considered equivalent substitutions and shall be included within the protection scope of the present invention.
Claims
1. A gallate-based near-infrared luminescent material exciteable by a blue LED, characterized in that, The molecular formula of the near-infrared luminescent material is Ba2M2NGa. 10-x Al x O 22 :yCr 3+ Where M is Sn, Zr or Hf, and N is Mg or Zn; 0 ≤ x ≤ 10; 0 < y ≤ 2.
2. The method for preparing gallium-based near-infrared luminescent material exciteable by blue LED according to claim 1, characterized in that, The specific steps include the following: S1. Mix and grind barium compound, M compound, N compound, gallium compound and / or aluminum compound, chromium compound and cosolvent boric acid until homogeneous to obtain a mixture; S2. The mixture is pre-calcined in air at 800-900°C, then ground after cooling to room temperature, and then calcined at 1400-1500°C to obtain a gallium-based near-infrared luminescent material that can be excited by blue LEDs.
3. The method for preparing gallium-based near-infrared luminescent materials exciteable by blue LEDs according to claim 2, characterized in that, The barium compound mentioned in step S1 is one or more of barium carbonate, barium nitrate, or barium oxide.
4. The method for preparing gallium-based near-infrared luminescent material exciteable by blue LED according to claim 2, characterized in that, The compound M mentioned in step S1 is tin nitrate, zirconium nitrate, hafnium nitrate, tin dioxide, zirconium dioxide, or hafnium dioxide.
5. The method for preparing gallium-based near-infrared luminescent material exciteable by blue LED according to claim 2, characterized in that, The N compound mentioned in step S1 is zinc carbonate, magnesium carbonate, zinc nitrate, magnesium nitrate, zinc oxalate, magnesium oxalate, zinc oxide, or magnesium oxide.
6. The method for preparing gallium-based near-infrared luminescent material exciteable by blue LED according to claim 2, characterized in that, The gallium compound in step S1 is one or more of gallium nitrate, gallium oxalate, or gallium oxide; the aluminum compound is one or more of aluminum nitrate, aluminum oxalate, or aluminum oxide.
7. The method for preparing gallium-based near-infrared luminescent material exciteable by blue LED according to claim 2, characterized in that, The chromium compound mentioned in step S1 is chromium nitrate and / or chromium oxide.
8. The method for preparing gallium-based near-infrared luminescent material exciteable by blue LED according to claim 2, characterized in that, The pre-calcination time in step S2 is 4 to 6 hours, and the calcination time is 6 to 8 hours.
9. The application of the gallate-based near-infrared luminescent material exciteable by blue LEDs as described in claim 1 in the field of blue LED chip fabrication.